El Excentrico, 1963-11-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
November 5, 1963 [5 de noviembre de 1963]. Ano 14, No 2. Cover has a picture of a man playing piano as four people watch him with enjoyment. The headline reads "Dinner Dance - Saturday Nov 16th - Rickeys Hyatt House."